(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
In developing countries, women are abused in many different areas. submission are in their nature because of the inequalities they face. Despite the explosive growth in education in many countries, women are still seen as equals between the sexes everywhere. The status of women is considered substandard even after they make significant contributions to society. This is the time for women to stand up for it. The topic of women's empowerment is a hot topic these days. Many NGOs work for the advancement of women and train them to be independent. The government also takes this issue very seriously and has announced several policies in favor of women. In this scenario, ICT also plays an important role. Through information technology, women gain security, awareness, knowledge, employment, trust, popularity, etc. This document highlights the role of ICT in empowering women. Several cases are discussed here to shed light on the changes ICT has brought to society. It also suggests step Empowering women through information technology.